Effect of elevated CO2 and small boat noise on the kinematics of predator–prey interactions. Issue 1875 (28th March 2018) - McCormick, Mark I.; Watson, Sue-Ann; Simpson, Stephen D.; Allan, Bridie J. M.
Abstract : Oceans of the future are predicted to be more acidic and noisier, particularly along the productive coastal fringe. This study examined the independent and combined effects of short-term exposure to elevated CO2 and boat noise on the predator–prey interactions of a pair of common coral reef fishes ( Pomacentrus wardi and its predator, Pseudochromis fuscus ). Successful capture of prey by predators was the same regardless of whether the pairs had been exposed to ambient control conditions, the addition of either playback of boat noise, elevated CO2 (925 µatm) or both stressors simultaneously. The kinematics of the interaction were the same for all stressor combinations and differed from the controls. The effects of CO2 or boat noise were the same, suggesting that their effects were substitutive in this situation. Prey reduced their perception of threat under both stressors individually and when combined, and this coincided with reduced predator attack distances and attack speeds. The lack of an additive or multiplicative effect when both stressors co-occurred was notable given the different mechanisms involved in sensory disruptions and highlights the importance of determining the combined effects of key drivers to aid in predicting community dynamics under future environmental scenarios.